Workshop report: National planning for phase 1 of the CCAC paddy rice component in Vietnam - Sander, Björn Ole (2015)
The objectives of this workshop are to 1) share experience on applying and scalling up the AWD technology for paddy rice in the Red river delta 2) identify key areas and aspects of work that need to be addressed and 3) develop a detailed national plan for phase I of CCAC-Rice component.